Mouse house hunter - Stilton, Geronimo; Dami, Elisabetta; Loizedda, Danilo, 1971- (New York, NY : Scholastic Inc., 2015)
Geronimo finds out that the Rodent Gazette is having money troubles and Grandfather William tells Geronimo that he must sell his home to save the paper.
"#61"--Spine.
"Based on an original idea by Elisabetta Dami"--T.p. verso.
Translation of: Geronimo cerca casa.
4.9
3-6.
3-6
Keywords: Stilton, Geronimo -- Juvenile fiction; Stilton, Geronimo -- Fiction; Stilton, Geronimo -- Fiction; House buying -- Juvenile fiction; Mice -- Juvenile fiction; House buying -- Fiction; Mice -- Fiction; Houses -- Buying and selling -- Fiction; Mice -- Fiction; Humorous fiction